A fire-proof and pressure-resistant composite rubber material for air springs

By using a composite flame retardant system with modified flame retardant loaded nano aluminum hydroxide in neoprene airbags, the problem of poor flame retardant performance of neoprene airbags is solved, and high fire resistance and pressure resistance and excellent pressure resistance at high temperatures are achieved.

CN118909331BActive Publication Date: 2025-02-28TAICANG GUANLIAN POLYMERIC MATERIAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411148509.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-02-28
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The existing neoprene airbags have poor flame retardant performance and cannot meet fire resistance requirements. At the same time, the large amount of addition of inorganic flame retardants will lead to a decrease in the fluidity and mechanical properties of the material, and the pressure resistance is also limited.

Method used

A composite flame retardant system is adopted to load nano aluminum hydroxide by modifying flame retardant to form a flame retardant and compressive additive with modified properties, and blend it with neoprene and reinforcement, plasticizer and other raw materials to improve the fire resistance and pressure resistance of the material.

Benefits of technology

The high fire-proof and pressure resistance of neoprene airbags is achieved. During fire, neoprene combustion is suppressed by "sacrificing oneself" to protect its molecular network structure integrity, while maintaining good pressure resistance at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005002904520000021
    Figure BDA0005002904520000021
  • Figure BDA0005002904520000031
    Figure BDA0005002904520000031
  • Figure BDA0005002904520000032
    Figure BDA0005002904520000032
Patent Text Reader

Abstract

The invention relates to a fireproof and pressure-resistant composite rubber material for an air spring, belonging to the technical field of polymer material modification. The composite rubber material comprises 100 parts of chloroprene rubber, 20-30 parts of a flame retardant and pressure-resistant additive, 50-70 parts of a reinforcing agent, 20-25 parts of a plasticizer, 3-5 parts of a vulcanizing agent, 2-3 parts of an accelerator and 0.5-0.8 parts of an antioxidant in parts by weight. The flame retardant and pressure-resistant additive is a composite flame retardant system formed by synergistically loading nano aluminum hydroxide on a modified flame retardant. When a fire occurs, a phosphorus-containing group is generated in the composite flame retardant system, which promotes the preferential degradation of its own polymer structure to form an organic expanded carbon layer as a barrier, and inhibits the combustion and carbonization of the chloroprene rubber by "sacrificing itself", thereby protecting the structural integrity of a molecular network of the chloroprene rubber. The flame retardancy of a chloroprene rubber matrix can be improved while the pressure resistance of the chloroprene rubber matrix at high temperatures can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material modification, and in particular relates to a fire-proof and pressure-resistant composite rubber material for air springs. Background Art

[0002] Air spring is a curved capsule made of rubber and mesh wire, commonly known as air tire, corrugated air tire, air bag, leather tiger, etc. The two ends of the capsule need to be connected with two steel plates to form a compressed air chamber. The rubber and mesh wire themselves do not provide load-bearing capacity, but the compressed air filled in the capsule completes it. The key component of the air spring is the rubber air bag, which is composed of an outer rubber layer, a cord layer and an inner rubber layer. The outer rubber layer is a protective layer used to isolate the contact between the cord layer and external factors such as ozone and oxygen to prevent the aging of the cord layer rubber. The cord layer is the pressure-bearing layer of the rubber spring, and there are multiple layers of nylon cord as the skeleton material. The inner rubber layer is an airtight layer. At present, chloroprene rubber is mostly used as the rubber material of the rubber air bag, but due to the poor flame retardant properties of chloroprene rubber, it cannot meet its flame retardant effect as a rubber air bag.

[0003] In the prior art, flame retardants are usually added to increase the flame retardant properties of chloroprene rubber. Aluminum hydroxide is the inorganic flame retardant additive with the largest amount and the widest application. As a flame retardant, it can not only retard flames, but also suppress smoke, and does not produce dripping and toxic gases, and has a good flame retardant effect. However, aluminum hydroxide, as an inorganic filler, has poor compatibility with the matrix, and needs to be added in large quantities to effectively exert the flame retardant effect. However, after a large amount of inorganic fillers are added, the fluidity of chloroprene rubber will be poor during mixing and molding, and the processing and mechanical properties of synthetic materials will be poor, resulting in a decrease in its pressure resistance, thereby limiting its use; while organic phosphorus flame retardants have less mechanical properties for rubber and have good compatibility with rubber. However, when a fire occurs, organic phosphorus flame retardants promote carbonization of the chloroprene rubber matrix through pyrolysis to suppress combustion. Although the flame retardant properties of chloroprene rubber are improved, chloroprene rubber is easy to become brittle, resulting in poor pressure resistance, which also limits its use. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a fire-proof and pressure-resistant composite rubber material for air springs;

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A fireproof and pressure-resistant composite rubber material for air springs, comprising the following raw materials in parts by weight:

[0007] 100 parts of chloroprene rubber, 20-30 parts of flame retardant and anti-compression additives, 50-70 parts of reinforcing agent, 20-25 parts of plasticizer, 3-5 parts of vulcanizing agent, 2-3 parts of accelerator and 0.5-0.8 parts of antioxidant;

[0008] Preparation of flame retardant and anti-compression additives:

[0009] Step A1: 2,5-dihydroxyterephthalic acid, DCC, DMAP and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 200-300 r / min, the temperature was raised to 25-35° C., the mixture was stirred for 30 min, oleylamine was added, the mixture was stirred for 5-6 h, the mixture was washed with water 3 times and then dried to obtain intermediate 1;

[0010] Further, the usage ratio of 2,5-dihydroxyterephthalic acid, oleylamine, DCC, DMAP and THF is 0.1 mol: 0.2 mol: 1.5-2 g: 0.1 g: 100 mL;

[0011] In step A1, the carboxyl group in 2,5-dihydroxyterephthalic acid and the amino group in oleylamine undergo amidation reaction to graft an unsaturated long alkyl chain onto 2,5-dihydroxyterephthalic acid. The specific structure is shown below:

[0012]

[0013] Step A2: dissolving epichlorohydrin, boron trifluoride etherate and carbon tetrachloride in a reaction kettle, controlling the stirring reaction rate to be 150-200 r / min, heating to 60-65° C., stirring and preserving for 20 minutes, then adding intermediate 1, then stirring and preserving for 3-4 hours, then adding 25% by mass sodium hydroxide solution, heating to 70° C., continuing to stir and preserving for 2 hours, then filtering to remove the precipitate, and then performing reduced pressure rotary evaporation to obtain intermediate 2;

[0014] Further, the usage ratio of epichlorohydrin, intermediate 1, boron trifluoride etherate, sodium hydroxide solution and carbon tetrachloride is 0.2 mol: 0.1 mol: 0.8-1.2 g: 6 mL: 150 mL;

[0015] In step A2, epichlorohydrin is ring-opened under the catalytic action of boron trifluoride ether to form chlorohydrin, which is then reacted with intermediate 1, and then HCl is removed under alkaline conditions, and the ring is closed to introduce an epoxy group. The structural formula is as follows:

[0016]

[0017] Step A3: DOPO, triphenylphosphine and DMF are mixed and added to a reactor, the stirring reaction rate is controlled to be 200-300 r / min, and the temperature is raised to 100-110° C. under nitrogen protection, and then intermediate 2 is added to the reactor, and the reaction is stirred and reacted for 1-2 hours, and then washed with water 2-3 times and dried to obtain intermediate 3;

[0018] Furthermore, the usage ratio of DOPO, intermediate 2, triphenylphosphine, and DMF is 0.2 mol: 0.1 mol: 0.5-0.8 g: 200 mL;

[0019] In step A3, PH in DOPO can react with the epoxy group in intermediate 2 and be grafted into intermediate 2, and its structure is as follows:

[0020]

[0021] Step A4: taking intermediate 3, hexamethylene diisocyanate, DBTDL and DMF, mixing and feeding into a reaction kettle, controlling the stirring reaction rate to be 300-500 r / min, heating to 70-80°C, stirring and reacting for 3-4 hours, washing with water and drying to obtain a modified flame retardant;

[0022] Further, the usage ratio of intermediate 3, hexamethylene diisocyanate, DBTDL and DMF is 0.1 mol: 0.1 mol: 1.5-2 g: 500 mL;

[0023] In step A4, the hydroxyl group in the intermediate 3 reacts with the isocyanate group in the hexamethylene diisocyanate to form a modified flame retardant;

[0024] Step A5: dispersing nano aluminum hydroxide in an ethanol solution, controlling the stirring reaction rate to be 500-800 r / min, then adding hydrochloric acid and mercaptopropyltrimethoxysilane, heating to 80° C., stirring and reacting for 3 hours, filtering, washing and drying to obtain modified aluminum hydroxide; then mixing the modified aluminum hydroxide and the modified flame retardant and feeding them into THF, irradiating them under 365 nm ultraviolet light for 24 hours and then drying to obtain a flame retardant and pressure-resistant additive;

[0025] Further, the usage ratio of nano aluminum hydroxide, hydrochloric acid, mercaptopropyltrimethoxysilane and ethanol solution is 15-20 g: 2 mL: 0.4 g: 100 mL; the usage ratio of modified aluminum hydroxide, modified flame retardant and THF is 15-20 g: 50 g: 200 mL;

[0026] In step A5, the surface of nano-aluminum hydroxide is first modified by mercaptopropyltrimethoxysilane to introduce mercapto groups into the surface of nano-aluminum hydroxide, and then a click reaction is carried out with the double bonds on the modified flame retardant to load the modified flame retardant to form a flame retardant and anti-compression additive;

[0027] Preparation of a fire-proof and pressure-resistant composite rubber material for air springs:

[0028] Step S1: adding chloroprene rubber, flame retardant and compression-resistant additives, reinforcing agent, plasticizer, vulcanizing agent, accelerator and antioxidant into a mixing agitator, stirring evenly to obtain a mixture, and then transferring the mixture into a rubber mixer at a mixing temperature of 90-100° C., and mixing for 30 minutes to obtain a rubber material;

[0029] Step S2: transferring the rubber material to a vulcanizer, controlling the vulcanization temperature to be 150-160° C., and vulcanizing for 15-20 minutes to obtain a fire-resistant and pressure-resistant composite rubber material for air springs.

[0030] Beneficial effects of the present invention:

[0031] The invention discloses a fireproof and pressure-resistant composite rubber material for air springs. The composite rubber material takes chloroprene rubber as a matrix and is mixed with a flame-retardant and pressure-resistant additive. Compared with common chloroprene rubber, the composite rubber material has higher fireproof and pressure-resistant performance. The flame-retardant and pressure-resistant additive is a composite flame-retardant system synergistically formed by a modified flame retardant loaded with nano-aluminum hydroxide. When a fire occurs, phosphorus-containing groups are generated in the composite flame-retardant system to promote the preferential degradation of its own polymer structure to form an organic expanded carbon layer as a barrier. The combustion and carbonization of the chloroprene rubber are inhibited by "sacrificing itself" to protect the structural integrity of the molecular network of the chloroprene rubber. The flame retardancy of the chloroprene rubber matrix can be improved while the pressure resistance of the chloroprene rubber matrix at high temperatures can be improved. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] 1) The flame retardant and anti-compression additive is prepared by the following method:

[0035] a1: 2,5-dihydroxyterephthalic acid, DCC, DMAP and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 200r / min, the temperature was raised to 25°C, and oleylamine was added after being kept warm and stirred for 30min. After being kept warm and stirred for 6h, the intermediate 1 was washed with water 3 times and dried to obtain the intermediate 1; in the above reaction, the amount ratio of 2,5-dihydroxyterephthalic acid, oleylamine, DCC, DMAP and THF was 0.1mol:0.2mol:1.5g:0.1g:100mL;

[0036] a2: dissolve epichlorohydrin, boron trifluoride etherate and carbon tetrachloride in a reaction kettle, control the stirring reaction rate to 150r / min, heat to 60°C, keep stirring for 20min, then add intermediate 1, keep stirring for 3h, then add 25% sodium hydroxide solution, heat to 70°C, keep stirring for 2h, filter to remove the precipitate, and then perform vacuum rotary evaporation to obtain intermediate 2; in the above reaction, the amount ratio of epichlorohydrin, intermediate 1, boron trifluoride etherate, sodium hydroxide solution and carbon tetrachloride is 0.2mol:0.1mol:0.8g:6mL:150mL;

[0037] a3: DOPO, triphenylphosphine and DMF were mixed and added to a reactor, the stirring reaction rate was controlled to be 200 r / min, and the temperature was raised to 100°C under nitrogen protection, and then intermediate 2 was added to the reactor, and the mixture was stirred and reacted for 1 hour, and then washed with water twice and dried to obtain intermediate 3; in the above reaction, the dosage ratio of DOPO, intermediate 2, triphenylphosphine and DMF was 0.2 mol: 0.1 mol: 0.5 g: 200 mL;

[0038] a4: intermediate 3, hexamethylene diisocyanate, DBTDL and DMF were mixed and added into a reactor, the stirring reaction rate was controlled to be 300 r / min, the temperature was raised to 70°C, the mixture was stirred and reacted for 3 hours, and then the modified flame retardant was washed and dried to obtain the modified flame retardant; in the above reaction, the amount ratio of intermediate 3, hexamethylene diisocyanate, DBTDL and DMF was 0.1 mol: 0.1 mol: 1.5 g: 500 mL;

[0039] a5: Take nano aluminum hydroxide (both the present embodiment and the comparative example use aluminum hydroxide produced by Ningbo Jiwei Nano New Material Technology Co., Ltd., model JWN-AOH-2N01) and disperse it in an ethanol solution with a mass fraction of 60%, control the stirring reaction rate to 500r / min, then add hydrochloric acid and mercaptopropyltrimethoxysilane, heat to 80°C, keep stirring and react for 3 hours, filter, wash and dry to obtain modified aluminum hydroxide; then mix the modified aluminum hydroxide and the modified flame retardant and feed them into THF, irradiate under 365nm ultraviolet light for 24 hours and then dry to obtain a flame retardant and pressure-resistant additive; in the above reaction, the amount ratio of nano aluminum hydroxide, hydrochloric acid, mercaptopropyltrimethoxysilane and ethanol solution is 15g:2mL:0.4g:100mL; the amount ratio of modified aluminum hydroxide, modified flame retardant and THF is 15g:50g:200mL;

[0040] 2) Preparing a fire-resistant and pressure-resistant composite rubber material for an air spring, comprising the following steps:

[0041] s1: 100 parts of chloroprene rubber (the present embodiment and the comparative example both use chloroprene rubber produced by Dongguan Xin Synthetic Rubber Co., Ltd., model CR2444), 20 parts of flame retardant and compression-resistant additives (the present embodiment uses the flame retardant and compression-resistant additives in Example 1), 20 parts of plasticizers (the present embodiment and the comparative example both use butylene phthalate), 50 parts of reinforcing agent (the present embodiment both use fast extrusion carbon black N550 and semi-reinforced carbon black N774 with a mass ratio of 2:3), 3 parts of vulcanizing agent (the present embodiment and the comparative example both use zinc oxide), 2 parts of accelerator (the present embodiment and the comparative example both use diphenylthiourea), and 0.5 parts of antioxidant (the present embodiment and the comparative example both use antioxidant 4020) are added into a mixing agitator, stirred evenly to obtain a mixture, and then the mixture is transferred to a rubber mixer, the rubber mixing temperature is 90°C, and the rubber is mixed for 30 minutes to obtain a rubber compound;

[0042] s2: The rubber material is transferred to a vulcanizer and the vulcanization temperature is controlled at 150°C. After vulcanization for 15 minutes, the fire-resistant and pressure-resistant composite rubber material for air springs is obtained.

[0043] Example 2

[0044] 1) The flame retardant and anti-compression additive is prepared by the following method:

[0045] a1: 2,5-dihydroxyterephthalic acid, DCC, DMAP and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 250r / min, the temperature was raised to 30°C, oleylamine was added after being kept warm and stirred for 30min, the mixture was kept warm and stirred for 6h, and then the mixture was washed with water 3 times and dried to obtain intermediate 1; in the above reaction, the dosage ratio of 2,5-dihydroxyterephthalic acid, oleylamine, DCC, DMAP and THF was 0.1mol:0.2mol:1.7g:0.1g:100mL;

[0046] a2: Dissolve epichlorohydrin, boron trifluoride etherate and carbon tetrachloride in a reaction kettle, control the stirring reaction rate to 200r / min, heat to 63°C, keep stirring for 20min, then add intermediate 1, keep stirring for 3h, then add 25% sodium hydroxide solution, heat to 70°C, keep stirring for 2h, filter to remove the precipitate, and then perform vacuum rotary evaporation to obtain intermediate 2; in the above reaction, the amount ratio of epichlorohydrin, intermediate 1, boron trifluoride etherate, sodium hydroxide solution and carbon tetrachloride is 0.2mol:0.1mol:0.9g:6mL:150mL;

[0047] a3: DOPO, triphenylphosphine and DMF were mixed and added to a reactor, the stirring reaction rate was controlled to be 250r / min, and the temperature was raised to 100°C under nitrogen protection, and then intermediate 2 was added to the reactor, and the reaction was stirred and reacted for 1 hour, and then washed with water twice and dried to obtain intermediate 3; in the above reaction, the dosage ratio of DOPO, intermediate 2, triphenylphosphine and DMF was 0.2mol:0.1mol:0.6g:200mL;

[0048] a4: intermediate 3, hexamethylene diisocyanate, DBTDL and DMF were mixed and added into a reactor, the stirring reaction rate was controlled to be 400r / min, the temperature was raised to 75°C, the mixture was stirred and reacted for 3h, and then the modified flame retardant was washed and dried to obtain the modified flame retardant; in the above reaction, the amount ratio of intermediate 3, hexamethylene diisocyanate, DBTDL and DMF was 0.1mol:0.1mol:1.7g:500mL;

[0049] a5: Take nano aluminum hydroxide and disperse it in a 60% ethanol solution, control the stirring reaction rate to 600r / min, then add hydrochloric acid and mercaptopropyltrimethoxysilane, heat to 80°C, keep stirring and react for 3 hours, filter, wash and dry to obtain modified aluminum hydroxide; then mix the modified aluminum hydroxide and the modified flame retardant and feed them into THF, irradiate under 365nm ultraviolet light for 24 hours and then dry to obtain a flame retardant and pressure-resistant additive; in the above reaction, the dosage ratio of nano aluminum hydroxide, hydrochloric acid, mercaptopropyltrimethoxysilane and ethanol solution is 17g:2mL:0.4g:100mL; the dosage ratio of modified aluminum hydroxide, modified flame retardant and THF is 17g:50g:200mL;

[0050] 2) Preparing a fire-resistant and pressure-resistant composite rubber material for an air spring, comprising the following steps:

[0051] s1: 100 parts of chloroprene rubber, 24 parts of flame retardant and anti-compression additives (the flame retardant and anti-compression additives in Example 2 are selected in this example), 60 parts of reinforcing agent, 22 parts of plasticizer, 4 parts of vulcanizing agent, 2.5 parts of accelerator and 0.6 parts of antioxidant are added to a mixing agitator, and the mixture is obtained after being stirred evenly. The mixture is then transferred to a rubber mixer, the mixing temperature is 100° C., and the rubber is mixed for 30 minutes to obtain a rubber compound;

[0052] s2: The rubber material is transferred to a vulcanizer and the vulcanization temperature is controlled at 155°C. After vulcanization for 15 minutes, the fire-resistant and pressure-resistant composite rubber material for air springs is obtained.

[0053] Example 3

[0054] 1) The flame retardant and anti-compression additive is prepared by the following method:

[0055] a1: 2,5-dihydroxyterephthalic acid, DCC, DMAP and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 300r / min, the temperature was raised to 35°C, and oleylamine was added after being kept warm and stirred for 30min. After being kept warm and stirred for 6h, the mixture was washed with water 3 times and dried to obtain intermediate 1. In the above reaction, the dosage ratio of 2,5-dihydroxyterephthalic acid, oleylamine, DCC, DMAP and THF was 0.1mol:0.2mol:1.8g:0.1g:100mL.

[0056] a2: dissolve epichlorohydrin, boron trifluoride etherate and carbon tetrachloride in a reaction kettle, control the stirring reaction rate to 200r / min, heat to 65°C, keep stirring for 20min, then add intermediate 1, keep stirring for 3h, then add 25% sodium hydroxide solution, heat to 70°C, keep stirring for 2h, filter to remove the precipitate, and then perform vacuum rotary evaporation to obtain intermediate 2; in the above reaction, the amount ratio of epichlorohydrin, intermediate 1, boron trifluoride etherate, sodium hydroxide solution and carbon tetrachloride is 0.2mol:0.1mol:1.0g:6mL:150mL;

[0057] a3: DOPO, triphenylphosphine and DMF were mixed and added to a reactor, the stirring reaction rate was controlled to be 250r / min, and the temperature was raised to 110°C under nitrogen protection, and then intermediate 2 was added to the reactor, and the mixture was stirred and reacted for 1 hour, and then washed with water twice and dried to obtain intermediate 3; in the above reaction, the dosage ratio of DOPO, intermediate 2, triphenylphosphine and DMF was 0.2mol:0.1mol:0.7g:200mL;

[0058] a4: intermediate 3, hexamethylene diisocyanate, DBTDL and DMF were mixed and added into a reactor, the stirring reaction rate was controlled to be 400r / min, the temperature was raised to 80°C, the mixture was stirred and reacted for 3h, and then the modified flame retardant was washed and dried to obtain the modified flame retardant; in the above reaction, the amount ratio of intermediate 3, hexamethylene diisocyanate, DBTDL and DMF was 0.1mol:0.1mol:1.8g:500mL;

[0059] a5: Take nano aluminum hydroxide and disperse it in a 60% ethanol solution, control the stirring reaction rate to 700r / min, then add hydrochloric acid and mercaptopropyltrimethoxysilane, heat to 80°C, keep stirring and react for 3 hours, filter, wash and dry to obtain modified aluminum hydroxide; then mix the modified aluminum hydroxide and the modified flame retardant and feed them into THF, irradiate under 365nm ultraviolet light for 24 hours and then dry to obtain a flame retardant and pressure-resistant additive; in the above reaction, the dosage ratio of nano aluminum hydroxide, hydrochloric acid, mercaptopropyltrimethoxysilane and ethanol solution is 18g:2mL:0.4g:100mL; the dosage ratio of modified aluminum hydroxide, modified flame retardant and THF is 18g:50g:200mL;

[0060] 2) Preparing a fire-resistant and pressure-resistant composite rubber material for an air spring, comprising the following steps:

[0061] s1: 100 parts of chloroprene rubber, 26 parts of flame retardant and anti-compression additives (the flame retardant and anti-compression additives in Example 3 are selected in this embodiment), 65 parts of reinforcing agent, 23 parts of plasticizer, 5 parts of vulcanizing agent, 3 parts of accelerator and 0.7 parts of antioxidant are added to a mixing agitator, and the mixture is obtained after being stirred evenly. The mixture is then transferred to a rubber mixer, the mixing temperature is 100° C., and the rubber is mixed for 30 minutes to obtain a rubber material;

[0062] s2: The rubber material is transferred to a vulcanizer and the vulcanization temperature is controlled at 160°C. After vulcanization for 15 minutes, the fire-resistant and pressure-resistant composite rubber material for air springs is obtained.

[0063] Example 4

[0064] 1) The flame retardant and anti-compression additive is prepared by the following method:

[0065] a1: 2,5-dihydroxyterephthalic acid, DCC, DMAP and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 300r / min, the temperature was raised to 35°C, and oleylamine was added after being kept warm and stirred for 30min. After being kept warm and stirred for 6h, the mixture was washed with water 3 times and dried to obtain intermediate 1. In the above reaction, the dosage ratio of 2,5-dihydroxyterephthalic acid, oleylamine, DCC, DMAP and THF was 0.1mol:0.2mol:2g:0.1g:100mL.

[0066] a2: dissolve epichlorohydrin, boron trifluoride etherate and carbon tetrachloride in a reaction kettle, control the stirring reaction rate to 200r / min, heat to 65°C, keep stirring for 20min, then add intermediate 1, keep stirring for 3h, then add 25% sodium hydroxide solution, heat to 70°C, keep stirring for 2h, filter to remove the precipitate, and then perform vacuum rotary evaporation to obtain intermediate 2; in the above reaction, the amount ratio of epichlorohydrin, intermediate 1, boron trifluoride etherate, sodium hydroxide solution and carbon tetrachloride is 0.2mol:0.1mol:1.2g:6mL:150mL;

[0067] a3: DOPO, triphenylphosphine and DMF were mixed and added to a reactor, the stirring reaction rate was controlled to be 250r / min, the temperature was raised to 110°C under nitrogen protection, and then intermediate 2 was added to the reactor, the mixture was stirred and reacted for 1h, and then washed with water twice and dried to obtain intermediate 3; in the above reaction, the dosage ratio of DOPO, intermediate 2, triphenylphosphine and DMF was 0.2mol:0.1mol:0.8g:200mL;

[0068] a4: intermediate 3, hexamethylene diisocyanate, DBTDL and DMF were mixed and added into a reactor, the stirring reaction rate was controlled to be 400r / min, the temperature was raised to 80°C, the mixture was stirred and reacted for 3h, and then the modified flame retardant was washed and dried to obtain the modified flame retardant; in the above reaction, the amount ratio of intermediate 3, hexamethylene diisocyanate, DBTDL and DMF was 0.1mol:0.1mol:2g:500mL;

[0069] a5: Take nano aluminum hydroxide and disperse it in a 60% ethanol solution, control the stirring reaction rate to 800r / min, then add hydrochloric acid and mercaptopropyltrimethoxysilane, heat to 80°C, keep stirring and react for 3 hours, filter, wash and dry to obtain modified aluminum hydroxide; then mix the modified aluminum hydroxide and the modified flame retardant and feed them into THF, irradiate under 365nm ultraviolet light for 24 hours and then dry to obtain a flame retardant and pressure-resistant additive; in the above reaction, the dosage ratio of nano aluminum hydroxide, hydrochloric acid, mercaptopropyltrimethoxysilane and ethanol solution is 20g:2mL:0.4g:100mL; the dosage ratio of modified aluminum hydroxide, modified flame retardant and THF is 20g:50g:200mL;

[0070] 2) Preparing a fire-resistant and pressure-resistant composite rubber material for an air spring, comprising the following steps:

[0071] s1: 100 parts of chloroprene rubber, 30 parts of flame retardant and anti-compression additives (the flame retardant and anti-compression additives in Example 4 are selected in this example), 70 parts of reinforcing agent, 25 parts of plasticizer, 5 parts of vulcanizing agent, 3 parts of accelerator and 0.8 parts of antioxidant are added to a mixing agitator, and the mixture is obtained after being stirred evenly. The mixture is then transferred to a rubber mixer, the mixing temperature is 90° C., and the rubber is mixed for 30 minutes to obtain a rubber compound;

[0072] s2: The rubber material is transferred to a vulcanizer and the vulcanization temperature is controlled at 150°C. After vulcanization for 15 minutes, the fire-resistant and pressure-resistant composite rubber material for air springs is obtained.

[0073] Comparative Example 1

[0074] A preparation method of a fireproof and pressure-resistant composite rubber material for an air spring comprises the following steps:

[0075] 1) Preparation of DOPO modified aluminum hydroxide flame retardant

[0076] a1: DOPO and aluminum hydroxide are mixed and added to toluene to form a suspension, and then triethylamine is added as a catalyst, and heated to reflux at 110-130°C for 6 hours. Filter, and then wash repeatedly with toluene to remove unreacted DOPO, and finally vacuum dry to obtain DOPO modified aluminum hydroxide flame retardant; in the above reaction, the dosage ratio of DOPO, aluminum hydroxide, triethylamine and toluene is 2g:5g:0.5mL:150mL;

[0077] 2) Preparing a fire-resistant and pressure-resistant composite rubber material for an air spring, comprising the following steps:

[0078] s1: 100 parts of chloroprene rubber, 26 parts of DOPO modified aluminum hydroxide flame retardant, 60 parts of reinforcing agent, 5 parts of vulcanizing agent, 3 parts of accelerator and 0.8 parts of antioxidant are added into a mixing agitator, and mixed evenly to obtain a mixture, and then the mixture is transferred to a rubber mixer, the mixing temperature is 90°C, and the rubber is mixed for 30 minutes to obtain a rubber compound;

[0079] s2: The rubber material is transferred to a vulcanizer and the vulcanization temperature is controlled at 150°C. After vulcanization for 15 minutes, the fire-resistant and pressure-resistant composite rubber material for air springs is obtained.

[0080] Comparative Example 2

[0081] The specific implementation process of preparing a fire-resistant and pressure-resistant composite rubber material for an air spring in this comparative example is as follows:

[0082] s1: 100 parts of chloroprene rubber, 15 parts of DOPO flame retardant, 15 parts of modified aluminum hydroxide flame retardant, 5 parts of vulcanizing agent, 60 parts of reinforcing agent, 3 parts of accelerator and 0.8 parts of antioxidant are added into a mixing agitator, and mixed evenly to obtain a mixture, and then the mixture is transferred to a rubber mixer, the mixing temperature is 90°C, and the rubber is mixed for 30 minutes to obtain a rubber compound;

[0083] s2: The rubber material is transferred to a vulcanizer and the vulcanization temperature is controlled at 150°C. After vulcanization for 15 minutes, the fire-resistant and pressure-resistant composite rubber material for air springs is obtained.

[0084] The fireproof and pressure-resistant composite rubber materials for air springs prepared in Examples 1-4 and the composite rubber materials for air springs prepared in Comparative Examples 1-2 were used to prepare test samples according to GB / T10707-2008. The test samples had a size of 100 mm x (6.5 ± 0.5) mm and a thickness of (3 ± 0.25) mm, and were subjected to a limiting oxygen index test.

[0085] The fireproof and pressure-resistant composite rubber materials for air springs prepared in Examples 1-4 and the composite rubber materials for air springs prepared in Comparative Examples 1-2 were used to prepare test samples according to GB / T10707-2008 and subjected to a combustion performance test;

[0086] Withstand voltage test:

[0087] The fireproof and pressure-resistant composite rubber materials for air springs prepared in Examples 1-4 and the composite rubber materials for air springs prepared in Comparative Examples 1-2 were tested for the highest pressure until they were destroyed according to JI SD4101-1991;

[0088] High temperature withstand voltage test:

[0089] The fireproof and pressure-resistant composite rubber materials for air springs prepared in Examples 1-4 and the composite rubber materials for air springs prepared in Comparative Examples 1-2 were baked at 300° C. for 5 hours and then tested for the highest pressure until they were destroyed according to JI SD4101-1991; the specific test data are shown in Table 1:

[0090] Table 1

[0091]

[0092] It can be seen from the data in Table 1 that the fireproof and pressure-resistant composite rubber material for air springs prepared in Examples 1-4 has a limiting oxygen index of 37-41%, and a combustion performance grade of FV-0, which is significantly better than that of Comparative Examples 1-2. In the normal temperature pressure test, the pressure resistance value of the fireproof and pressure-resistant composite rubber material for air springs prepared in Examples 1-4 is 2.5-2.9Mpa, which is not much different from the pressure resistance value of Comparative Examples 1-2. However, after baking at 300°C, the pressure resistance value of the fireproof and pressure-resistant composite rubber material for air springs prepared in Examples 1-4 is 2.4-2.7Mpa, which is significantly better than that of Comparative Examples 1-2, indicating that the fireproof and pressure-resistant composite rubber material for air springs disclosed in the present invention not only has good flame retardancy, but also still has excellent pressure resistance after high-temperature baking.

[0093] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0094] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A fireproof and pressure-resistant composite rubber material for air springs, characterized in that: The composition comprises 100 parts of chloroprene rubber, 20-30 parts of flame retardant and compression-resistant additives, 50-70 parts of reinforcing agent, 20-25 parts of plasticizer, 3-5 parts of vulcanizing agent, 2-3 parts of accelerator and 0.5-0.8 parts of antioxidant according to weight parts; The flame retardant and compression-resistant additive is prepared by the following method: Step A1: 2,5-dihydroxyterephthalic acid, DCC, DMAP and THF were mixed and added, the temperature was raised to 25-35°C, the mixture was stirred for 30 minutes, oleylamine was added, the mixture was stirred for 5-6 hours, the mixture was washed with water 3 times and dried to obtain intermediate 1; Step A2: dissolving epichlorohydrin, boron trifluoride etherate and carbon tetrachloride in a reaction kettle, heating to 60-65°C, stirring at this temperature for 20 minutes, adding intermediate 1, stirring at this temperature for 3-4 hours, adding 25% by mass sodium hydroxide solution, heating to 70°C, stirring at this temperature for 2 hours, filtering the precipitate, and vacuum rotary evaporation to obtain intermediate 2; Step A3: DOPO, triphenylphosphine and DMF are mixed and added, and the temperature is raised to 100-110° C. under nitrogen protection, and then intermediate 2 is added to the reactor, and the mixture is stirred and reacted for 1-2 hours, and then washed with water and dried to obtain intermediate 3; Step A4: taking intermediate 3, hexamethylene diisocyanate, DBTDL and DMF, mixing and feeding, heating to 70-80°C, stirring and reacting for 3-4h, washing and drying to obtain a modified flame retardant; Step A5: dispersing nano aluminum hydroxide in an ethanol solution, then adding hydrochloric acid and mercaptopropyltrimethoxysilane, heating to 80° C., stirring and reacting for 3 hours, filtering, washing and drying to obtain modified aluminum hydroxide; then mixing the modified aluminum hydroxide and the modified flame retardant, adding them to THF, irradiating with ultraviolet light for 24 hours and drying to obtain a flame retardant and pressure-resistant additive; In step A1, the usage ratio of 2,5-dihydroxyterephthalic acid, oleylamine, DCC, DMAP and THF is 0.1 mol: 0.2 mol: 1.5-2 g: 0.1 g: 100 mL; In step A2, the amount ratio of epichlorohydrin, intermediate 1, boron trifluoride etherate, sodium hydroxide solution and carbon tetrachloride is 0.2 mol: 0.1 mol: 0.8-1.2 g: 6 mL: 150 mL; In step A3, the usage ratio of DOPO, intermediate 2, triphenylphosphine and DMF is 0.2 mol: 0.1 mol: 0.5-0.8 g: 200 mL; In step A4, the usage ratio of intermediate 3, hexamethylene diisocyanate, DBTDL and DMF is 0.1 mol: 0.1 mol: 1.5-2 g: 500 mL; In step A5, the dosage ratio of nano aluminum hydroxide, hydrochloric acid, mercaptopropyltrimethoxysilane and ethanol solution is 15-20g: 2mL: 0.4g: 100mL; the usage ratio of modified aluminum hydroxide, modified flame retardant and THF is 15-20g: 50g: 200mL; The method for preparing the fireproof and pressure-resistant composite rubber material for air springs is characterized by comprising the following steps: Step S1: adding chloroprene rubber, flame retardant and compression-resistant additives, reinforcing agent, plasticizer, vulcanizing agent, accelerator and antioxidant into a mixing agitator, stirring evenly to obtain a mixture, and then transferring the mixture into a rubber mixer at a mixing temperature of 90-100° C., and mixing for 30 minutes to obtain a rubber material; Step S2: transferring the rubber material to a vulcanizer, and vulcanizing for 15-20 minutes to obtain a fire-resistant and pressure-resistant composite rubber material for air springs.

2. The fireproof and pressure-resistant composite rubber material for air springs according to claim 1, characterized in that: The vulcanization temperature is 150-160℃.

Citation Information

Patent Citations

  • Environment-friendly low-smoke flame-retardant rubber composition as well as preparation method and application of environment-friendly low-smoke flame-retardant rubber composition

    CN105273267A

  • Efficient PP flame-retardant master batch and preparation method thereof

    CN113248831A

  • Fire-resistant bus duct based on epoxy resin and preparation method thereof

    CN117487318A